(untitled) (AYUSHDHARA, 2023)
Among the Panchvidha kashaya kalpana, Kwatha kalpana is the most significant dosage form in Ayurvedic pharmaceutics which is used worldwide. However it has some disadvantages like shorter shelf life, bitter taste and inconvenience in preparation, transportation and storage. To overcome these difficulties the Kwatha kalpana is being modified into Ghanvati without compromising the therapeutic efficacy. Shatiyadi kashaya ghanvati is a modified tablet form of the classical polyherbal formulation Shatiyadi kashaya. In this study, efforts have been made to establish analytical standards for two types of Shatiyadi kashaya ghanvati which were not available till date. Aims and objectives: To prepare two types of Shatiyadi kashaya ghanvati as mentioned in classical texts and do the comparative analysis of their physico-chemical properties. Materials And Methods: The study involves the preparation of Shatiyadi kashaya as per Ayurvedic texts (type I acc. to Bhaishajya Ratnavali and type II acc. to Bharat Bhaishajya Ratnakar) which was then modified into Ghanvati. Thereafter samples of Shatiyadi kashaya ghanvati type I and type II were taken for the comparative pharmaceutical and physicochemical study. Result and Conclusion: The physico-chemical analysis of two types of Shatiyadi kashaya ghanvati revealed that all test parameters were within API limits which ensure the safety and purity of the drug.